Pengaruh Waktu Pemupukan Daun dan Penyiangan Gulma terhadap Pertumbuhan dan Hasil Gambas pada Tanah Spodosol - Ruben Tinting Sirenden; Titin Apung Atikah; Vera Amalia (Universitas Gadjah Mada, 2026)
This research aims to determine the effects of fertilization timing and weed control on the growth and yield of Sponge Gourd, and to identify the best timing for optimal growth and yield. The research was conducted from April - July 2024 on a farmer's land at Palangka Raya, Central Kalimantan. The method used was a Randomized Block Design (RBD) with 10 treatment combinations and 3 groups. Treatments included fertilization with Gandasil B at 20 and 23 days after planting (DAP), 25 and 28 DAP, and 30 and 33 DAP, along with weed control intervals of 7, 14, and 21 days. Observed variables were plant length, number of leaves, number of branches, fruit diameter, fruit length, fresh weight of sample fruit, number of sample fruits, fresh weight of fruit per plot, and number of fruits per plot. The results showed significant differences in fertilization timing and weed control on plant length, number of leaves, number of branches, fresh weight of sample fruit, number of sample fruits, fresh weight of fruit per plot, and number of fruits per plot, but no significant differences in fruit diameter and length. Weed vegetation analysis indicated that babadotan weeds had the highest Summed Dominance Ratio (SDR) of 26% before land preparation, and jukut pendul weeds had the highest SDR of 45% post-harvest. Treatment G4, with fertilization at 25 and 28 DAP and weed control every 7 days, was the best treatment. Observations showed that all variables in treatment G4 had the highest average values.